Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.3382/ps.2010-00686
|View full text |Cite
|
Sign up to set email alerts
|

Changes in hepatic lipid parameters and hepatic messenger ribonucleic acid expression following estradiol administration in laying hens (Gallus domesticus)

Abstract: Fatty liver hemorrhagic syndrome (FLHS) is characterized by increased hepatic triacylglycerol content associated with liver hemorrhages and results in a sudden decline in egg production. Genetic, environmental, nutritional, and hormonal factors have all been implicated in the etiology of FLHS, but the exact cause of FLHS is still unknown. Estrogens have been implicated in the development of excess fat content of the liver and in the etiology of FLHS. This study investigated estradiol (E(2)) administration in h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 42 publications
3
29
0
Order By: Relevance
“…Previous reports demonstrated lead exposure could change lipid metabolism in chickens, increasing liver cholesterol levels that cause fatty liver issues (Lawton and Donaldson, 1991;Bruggeman et al, 1999;Cave et al, 2010). Lipid accumulated in the liver resulted in an imbalance in nutrition and fatty liver syndrome by changing the rate of hepatic lipogenesis in chickens (Lee et al, 2010). In this respect, our results indicate that heavier liver weight resulted from the slight alteration of fat content in the liver.…”
Section: Discussionsupporting
confidence: 51%
“…Previous reports demonstrated lead exposure could change lipid metabolism in chickens, increasing liver cholesterol levels that cause fatty liver issues (Lawton and Donaldson, 1991;Bruggeman et al, 1999;Cave et al, 2010). Lipid accumulated in the liver resulted in an imbalance in nutrition and fatty liver syndrome by changing the rate of hepatic lipogenesis in chickens (Lee et al, 2010). In this respect, our results indicate that heavier liver weight resulted from the slight alteration of fat content in the liver.…”
Section: Discussionsupporting
confidence: 51%
“…Hepatic steatosis in layers tends to occur most often where there is an imbalance in the protein/ energy ratio and causes a drop in egg production and obese hens. Fatty liver haemorrhagic syndrome (FLHS) has also been observed in hens treated with oestrogens (Butler, 1976 ; Lee et al ., 2010 ; Choi et al ., 2012 ). This disease, which is not to be confused with hepatic steatosis, is almost invariably fatal but it can also affect egg production (Walzem et al ., 1993 ; Lee et al ., 2010 ).…”
Section: Nutritional Challenges – Prevention Of Metabolic Diseasementioning
confidence: 99%
“…Fatty liver haemorrhagic syndrome (FLHS) has also been observed in hens treated with oestrogens (Butler, 1976 ; Lee et al ., 2010 ; Choi et al ., 2012 ). This disease, which is not to be confused with hepatic steatosis, is almost invariably fatal but it can also affect egg production (Walzem et al ., 1993 ; Lee et al ., 2010 ). The provision of dietary 25 (OH) D3, feed restriction with substitution of carbohydrate by dietary fat, supplementation of choline, inositol, vitamin B12, folic acid and vitamin E in the diet have all been shown to limit the incidence of hepatic steatosis and FLHS in layers (Bouvarel and Nys, 2013 ).…”
Section: Nutritional Challenges – Prevention Of Metabolic Diseasementioning
confidence: 99%
“…Our data indicated the secretion of VLDL from SE-infected LMH-2A cells reduced (Figure 4(a)) and the lipid accumulation in hepatocytes increased (Figure 1(a),(b)). Lee et al (2010) indicated that excessive triacylglycerol deposited in the hepatocytes of laying hens reduced egg production. We speculate that SE infection leads to excessive lipid accumulation in the LMH-2A cells and it may then have impact on egg production.…”
Section: Discussionmentioning
confidence: 99%